Econometric Modeling and Forecasting of Food Exports in Albania - Braimllari (Spaho), Alma; Oltiana Toshkollari (European Journal of Multidisciplinary Studies, 2016)
Exports of goods and services represent one of the most important sources of foreign exchange income that alleviate the pressure on the balance payment and create employment opportunities. Exports’ opportunities in Albania for food products have been increasing significantly, but still they are far from their real capacity. This study is an attempt to model and forecast the monthly export of food, beverages and tobacco products of Albania, using the seasonal autoregressive integrated moving average (SARIMA) methodology. The data used are covering the period 2005:M1-2015:M12, and are taken from the database of National Institute of Statistics of Albania. Unit root tests are used to test the stationarity of the series. Autocorrelation and partial autocorrelation functions are used to identify the most suitable SARIMA model, in explaining the time series and forecasting the future monthly food exports. The residuals of the best fitted model are used for the diagnostic checking. The results indicate that the best fitted model is SARIMA (3,1,1)x(1,1,0)12. The best identified model for the data in the study is used to forecast monthly food exports up to the year 2017. These findings are useful for customers, producers and policymakers.